1995
DOI: 10.1002/srin.199501166
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the behaviour of voids in steel plates during hot rolling

Abstract: The prime objective of the work is to predict the behaviour of voids in the steel slab during hot rolling and to assess the tendency of the void to closure, depending on the process parameters. The rigid-plastic thermal-mechanical finite-element program is used for the purpose. The model which simulates the general case of deformation of a single void in a matrix undergoing plastic deformation is developed. This model allows the investigation of the influence of the stress state on the void's behaviour. Finite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…It is explained by the fact that the temperature gradient induces more compressive stress states in the bulk of workpieces. Pietrzyk et al [12] confirmed the favourable effect of pre-cooling workpieces in hot rolling. Överstam and Jarl [10] also pointed out a coupled effect between friction and temperature regarding their effect on void closure.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…It is explained by the fact that the temperature gradient induces more compressive stress states in the bulk of workpieces. Pietrzyk et al [12] confirmed the favourable effect of pre-cooling workpieces in hot rolling. Överstam and Jarl [10] also pointed out a coupled effect between friction and temperature regarding their effect on void closure.…”
Section: Introductionmentioning
confidence: 77%
“…As a consequence, the values of closure coefficients B (respectively coefficients C) are given by a linear combination of bðγ 1 Þ, bðγ 2 Þ and bðγ 3 Þ (respectively cðγ 1 Þ, cðγ 2 Þ and cðγ 3 Þ), according to Eq. (12).…”
Section: Validation Of the Prediction Modelmentioning
confidence: 95%
See 1 more Smart Citation
“…The slab and/or the sheet in the roll gap were divided into three zones, and different kinematical admissible velocity fields were assumed for each zone. Pietrzick et al [15] used a rigid-plastic thermalmechanical finite-element program to examine the behavior of voids inside a steel slab during hot rolling and to assess the tendency of void closure. The effect of void shapes round and rectangular was studied by Dyi-Cheng Chen and Yeong-Maw Hwang [16].…”
Section: Casting Defects/voids and Their Closuresmentioning
confidence: 99%
“…Various methods, such as upper bound analysis [2][3][4][5] , finite element method [1,[6][7][8][9][10][11][12] and experimental investigation [12][13][14] are used to develop predictive measures for void closure during forging and rolling processes. In these studies, a few macroscopic voids are often introduced to analyze the deformation of voids.…”
Section: Introductionmentioning
confidence: 99%